Heterogeneous immune response following SARS-CoV-2 vaccination irrespective of diabetes status in a group of subjects- a pilot study - Mahbub, Chomel; Haque, Afrin; Hossain, Biplob; Tasnim, Sadia; Hassan, Zahid; Sultana, Rosy (Bangladesh Journal of Medical Science, 2025)
Objective This study aims to assess the rate of COVID-19 infection and IgG seroprevalence of SARS-COV-2 among diabetic and nondiabetic subjects. This evaluation provides insight into how diabetic subjects respond to the COVID-19 pandemic, shedding light on the strength and duration of their immune responses following vaccination. Materials and Methods This cross-sectional study included 90 volunteers (45 DM and 45 NDM subjects) from BIHS General Hospital, who have received at least one dose of COVID-19 vaccine. SARS CoV- 2 IgG antibody level was determined using ELISA. Data were analyzed using SPSS Version 26. Results and Discussion The SARS-CoV-2 IgG level was observed in both DM and NDM groups (14.48±11.6 and 14.31±11.45 BAU/mL) (BAU×104), with a gradual rise in antibody level by an increasing number of COVID-19 vaccine doses. No significant difference in respect to SARS-CoV-2 IgG antibody level was found between DM and NDM subjects (p=0.949). The rate of COVID-19 infection was found significantly higher in the non-diabetic group compared to the diabetic group (p=0.001). Among the BMI groups, a significantly higher level of IgG antibody was demonstrated among the obese population compared to normal and overweight groups (p=0.037). Conclusions Vaccination induced pronounced SARS-CoV-2 IgG response having no statistical difference in diabetic and non-diabetic groups. Heterogeneity in immune responses has been observed in both populations. The obese subjects had notably raised IgG levels. The incidence of COVID-19 infection was more higher in the nondiabetic compared to the diabetic group. BJMS, Vol. 24 No. 03 July’25 Page : 858-865